232k views
3 votes
Step : You should now have four terms
Directions: Factor each polynomial.
2x2 + 17x + 21

1 Answer

3 votes

Answer:

(x + 7)(2x + 3)

Explanation:

Given

2x² + 17x + 21

Consider the factors of the product of the x² term and the constant which sum to give the coefficient of the x- term.

product = 2 × 21 = 42 and sum = + 17

The factors are + 14 and + 3

Use these factors to split the x- term

2x² + 14x + 3x + 21 ( factor the first/second and third/fourth terms )

= 2x(x + 7) + 3(x + 7) ← factor out (x + 7) from each term

= (x + 7)(2x + 3) ← in factored form

User Dameion
by
4.7k points